Comparison of the Horizontal Positional Accuracy of Single-base and Network RTK within the Mega-Manila Sub-Network - Reyes, Rosalie; Braza, Clarizza Mae; Lim, Joy; Cayapan, Charisma Victoria (Philippine Engineering Journal, 2018)
Abstract – Real Time Kinematic (RTK) Global Navigation Satellite System (GNSS) survey is a reliable and efficient survey method that has been used in applications that require centimeter level positioning in real time since the late 1900s. Two methods are commonly used for RTK positioning namely single-base RTK (SBRTK) and network RTK (NRTK). This research assessed the horizontal positional accuracy of SBRTK and NRTK with respect to derived positions using static positioning method. The Philippine Active Geodetic Network (PageNET) stations of the National Mapping and Resource Information Authority (NAMRIA), specifically the stations belonging in the Mega-Manila sub-network, were used as reference stations. Five (5) points with increasing distance from PTAG station were tested for this study in SBRTK method. Three techniques in NRTK were also experimented, namely: Virtual Reference System (VRS), Master Auxiliary Concept (MAC) and Flächen-Korrektur Parameter (FKP).   The coordinates of the test points measured using RTK were evaluated by comparing with the coordinates of the same points observed in static mode. The results showed that NRTK techniques excepting MAC that is giving inconsistent results are better than SBRTK in distances more than 10 km from the base station PTAG. The FKP and VRS gave average coordinate differences of 5.64 cm and 5.63 cm, respectively, compared with the 6.61 cm coordinate difference of SBRTK for the five test points. The FKP NRTK and SBRTK provide the fastest initialization time of less than 30 seconds in most of the test sites. The VRS method gave almost similar coordinate difference average as the FKP method; however, the latter method had a faster initialization time with an average of 54 seconds as against 138 seconds for the former. The results also show the distance dependency of the accuracy of the SBRTK technique. The results ranged from 2.3 cm to 11.2 cm for distance range of 5.2 km to 23.3 km, respectively. Thus, NRTK is a better alternative to SBRTK because of this. However, SBRTK can provide faster initialization than other NRTK techniques.   The accuracies of the different RTK techniques were also assessed with respect to the geodetic control specifications of the Philippine Reference System of 1992 (PRS92) mandated as the standard reference system for all surveys in the Philippines in Executive Order No. 45, series of 1992, as amended. From the results, all RTK techniques gave less than 10 ppm linear error, which is the allowable error for first-order geodetic control survey. Therefore RTK techniques can supplant the use of Static post-processing (PP) method for first-order and lower accuracy surveys where productivity is a prime requirement.     Keywords—FKP, GNSS, MAC, Real-Time Kinematic, Single-base RTK, Network RTK, VRS